Two zinc ABC transporters contribute to Rhizobium leguminosarum symbiosis with Pisum sativum and Lens culinaris - Soldek, Joanna N.; Ballesteros-Gutiérrez, Marta; Díaz-Sáez, Laura; Delgado-Santamaría, Ignacio; Palacios, José Manuel; Albareda, Marta (Frontiers in Plant Science, 2025)
The establishment of the rhizobium-legume symbiosis requires adjusting the behavior of both partners to nodule conditions in which transition metals are delivered to the bacteria, as many rhizobial metalloenzymes are essential for bacteroid functions and symbiotic performance. A previous proteomic analysis revealed the existence of a relevant number of proteins differentially expressed in bacteroids induced by Rhizobium leguminosarum bv. viciae (Rlv) UPM791 in pea and lentil nodules. Among these proteins, a metal-binding protein (RLV_3444) component of an ABC-transporter system (RLV_3442-3444) was shown to be overexpressed in pea bacteroids, suggesting that metal provision to the bacteroid is more restrictive in the rhizobium-pea symbiosis. In this work, protein sequence analysis and structural modelling have revealed that RLV_3444 is highly similar to the functionally characterized zinc-binding protein ZniA from Klebsiella pneumoniae, so the host-dependent binding protein was renamed as ZniA and the transporter system as ZniCBA. The genome of Rlv UPM791 also encodes the conserved high-affinity ZnuABC transporter system. We demonstrate that at least one of the two systems must be present for Rlv to grow under zinc-limiting conditions and for optimal symbiotic performance with pea and lentil plants. The three conserved histidine residues present in multiple Zn2+-binding proteins have been shown as essential for the function of Rlv ZniA, and in-silico modelling suggests that they might participate in metal coordination. We also demonstrate that both ZniCBA and ZnuA are regulated by zinc in a Zur-dependent manner, consistent with the presence of a Zur box in their regulatory region. The expression patterns revealed that ZniCBA is expressed at lower levels than ZnuA, and its expression increased in a znuA mutant under both free-living and symbiotic conditions. These results, along with the observed increment in the expression of ZniCBA in pea versus lentil bacteroids, suggest that the host-dependent transporter system might play an auxiliary function for zinc uptake under zinc starvation conditions and might play a relevant role in the adaptation of rhizobia to the legume host.